Новый вид паразитических перепончатокрылых рода Echthroplexiella Mercet (Hymenoptera, Encyrtidae) из УССР и Молдавии - Тряпицын, В.А. (Вестник зоологии, 1980)
Edhthroplexiella talitzkyi sp. n. is described in the paper. The new species is closely related to E. phacelina T r j a p i t z i n from Tuva and Mongolia.